Reorganisation of the Right Occipito-Parietal Stream for Auditory Spatial Processing in Early Blind Humans. A Transcranial Magnetic Stimulation Study - Collignon, O; Davare, M; Olivier, E; De Volder, A. G (Brain topography, 2009)
It is well known that, following an early visual deprivation, the neural network involved in processing auditory spatial information undergoes a profound reorganization. In particular, several studies have demonstrated an extensive activation of occipital brain areas, usually regarded as essentially “visual”, when early blind subjects (EB) performed a task that requires spatial processing of sounds. However, little is known about the possible consequences of the activation of occipitals area on the function of the large cortical network known, in sighted subjects, to be involved in the processing of auditory spatial information. To address this issue, we used event-related transcranial magnetic stimulation (TMS) to induce virtual lesions of either the right intra-parietal sulcus (rIPS) or the right dorsal extrastriate occipital cortex (rOC) at different delays in EB subjects performing a sound lateralization task. Surprisingly, TMS applied over rIPS, a region critically involved in the spatial processing of sound in sighted subjects, had no influence on the task performance in EB. In contrast, TMS applied over rOC 50 ms after sound onset, disrupted the spatial processing of sounds originating from the contralateral hemifield. The present study shed new lights on the reorganisation of the cortical network dedicated to the spatial processing of sounds in EB by showing an early contribution of rOC and a lesser involvement of rIPS.